Penentuan Kriteria Dalam Penilaian Sub-Kontraktor Untuk Proses Blackening Dengan Pendekatan Analytical Hierarchy Process (AHP) Di PT. TKI - Andreamara Andreamara; Ikhsan Romli; Andriani Andriani (Prosiding Sains dan Teknologi, 2022)
TKI is a company in the manufacturing industry, with the main job of machining processes for motor vehicle components. PT. TKI has 2 sub-cons for blackening work and intends to evaluate those sub-cons. The method used to determine the assessment criteria using Analytical Hierarchy Process method (AHP). The results of the criteria research using the AHP method obtained 5 criteria, namely quality, price, delivery, flexibility, and responsiveness (QCDFR) with the weight of each criterion: quality = 0.48, price = 0.13, delivery = 0.31, flexibility = 0.05, and responsiveness = 0.03. These five criteria will then be used to evaluate the sub-contractors to be implemented at the end of the year. Keywords: AHP, Sub-Contractor, Criteria, Industry, Blackening